1966
DOI: 10.1111/j.1600-0765.1966.tb01842.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gingivitis in man

Abstract: After 9–21 days without oral hygiene eleven experimental subjects with previously excellent oral hygiene and healthy gingivae developed heavy accumulations of plaque and generalized mild gingivitis. The individual rate of development of gingivitis was closely correlated with the rate of plaque accumulation. Characteristic bacteriological changes were revealed in the plaque along the gingival margin during this experiment. Initially, i.e. when the teeth were clean and the gingiva healthy, the extremely sparse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 717 publications
(88 citation statements)
references
References 17 publications
2
82
1
3
Order By: Relevance
“…5 Hence, the emphasis was on a possible degenerative disease leading to bone resorption and tooth mobility. While the 1960s brought the evidence to confirm that dental plaque is the etiological factor of periodontal diseases, 6,7 crucial studies in the 1970s investigated a possible microbiological cause of what we now call AgP. As "non-specific" 8 and then "specific" 9 plaque hypotheses for periodontitis developed, it was now becoming clear that AgP was also a plaque-induced gingival disease.…”
Section: Agp-microbiological Studiesmentioning
confidence: 99%
“…5 Hence, the emphasis was on a possible degenerative disease leading to bone resorption and tooth mobility. While the 1960s brought the evidence to confirm that dental plaque is the etiological factor of periodontal diseases, 6,7 crucial studies in the 1970s investigated a possible microbiological cause of what we now call AgP. As "non-specific" 8 and then "specific" 9 plaque hypotheses for periodontitis developed, it was now becoming clear that AgP was also a plaque-induced gingival disease.…”
Section: Agp-microbiological Studiesmentioning
confidence: 99%
“…Some of the members of the 'yellow' complex of oral streptococci are candidates for this position. Plaque samples from healthy gingival sulci normally contain a large number of oral streptococci (Theilade et al, 1966). Socransky et al (1998) previously showed that yellow complexes, as a total, were associated with shallow pockets (probing depth of ,3 mm).…”
mentioning
confidence: 99%
“…The bacterial plaque in proximity to the gingival margin seems to be the essential agent, which plays a role in inducing gingival inflammation [1][2][3][4][6][7][8][9][10]12]. The body of evidence is consistent and stems from epidemiologic data, microbiologic research, immunologic studies, and clinical observations [1][2][3][4][6][7][8][9][10]12,30,31]. The study of experimental gingivitis by the withdrawal of all forms of oral hygiene performed by Löe, et al [1] inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…In periodontal disease, the risk factors may be defined as local environmental factors, behavioral factors in nature and systemic factors, which may be responsible in providing an ideal environment for bacterial colonization and/or fragility in a determinate tooth or teeth and adjacent periodontal tissues and/or interference in the inflammatory process [5,11,32,33]. Due to the association with risk factors, the opportunist endogenous bacteria, which are predominant in establishing gingival margin inflammation, also may induce destruction in the initial phase of periodontitis [1,2,8,10,17]. Periodontal disease could be considered as sequel of the inflammatory reaction, which must be always active, protecting individual against infection and possible septicemia, by bacteria present in the gingival sulcus, a critical area where junctional epithelium is an exclusive and fragile structure, separating connective tissue from an infected humid and warm oral environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation